Future trends in microelectronics : (Wiley-Interscience, 2007)
In this book leading profesionals in the semiconductor microelectronics field discuss the future evolution of their profession. The following are some of the questions discussed: Does CMOS technology have a real problem? Do transistors have to be smaller or just better and made of better materials? ....